If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x(x + -2) = 0 Reorder the terms: 6x(-2 + x) = 0 (-2 * 6x + x * 6x) = 0 (-12x + 6x2) = 0 Solving -12x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6x'. 6x(-2 + x) = 0 Ignore the factor 6.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2Solution
x = {0, 2}
| 2+2(5x-4)=7-5(2x+1) | | Y/3=96 | | 3n^2+24=22n | | 3.4/3 | | 3x+3[5x-7x]=12-x | | 31+z=13 | | M-87=101 | | 71/2-11/12 | | 35+x=43 | | 6.25=r | | 5n+7=6 | | -x(-x+5)=36 | | 40x^2+30x=10x | | X^2=40+3x | | 8+3(4x-5)=6-4(2x+1) | | 1/2(7x-2) | | 19=2w-17 | | 5(x+1)-3(x+6)=40 | | 4w-8=36 | | Y/10-5=-45 | | x^2-11x+180=0 | | 1/3x-1=-1 | | N/4-4=1 | | 2(14x+27y)-4(23x-7y)=236 | | 3(x+8)=6x+2-3x+22 | | a-3/2a3:a-1/a-2 | | 1/5y-3=1 | | 6y^2-14y+8=0 | | 2x+3y-x-[8+1]= | | w/3-9=20 | | 6x+3x+12(4x+3)=x | | 15-2w=5 |